PENGARUH INTERAKSI SOSIAL TEMAN SEBAYA TERHADAP KONSEP DIRI PESERTA DIDIK KELAS VIII DI SMP NEGERI 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Melani, Ulfa; Solina, Wira; Putri, Besti Nora Dwi (Jurnal Manajemen Pendidikan, 2025)
This research is motivated by the problem of poor peer social interaction in schools, which can have a negative impact on the formation of students' self-concept. Peer social interaction plays an important role in forming confidence, self-acceptance, and healthy social relationships. This study aims to describe: (1) the social interaction profile of peers, (2) the profile of self-concept, and (3) the influence of social interaction of peers on the self-concept of students. The type of research is quantitative with a correlational method. The research population was 70 people, with a simple random sampling technique so that 41 samples were obtained. The research instrument is in the form of a questionnaire, while the data analysis uses simple linear regression. The results showed that: (1) the social interaction of students' peers was in the poor category, (2) students' self-concept was in the poor category, and (3) there was a significant influence of social interaction of peers on self-concept by 94.7% with a very strong category. Based on these findings, BK teachers are advised to facilitate activities that increase students' social interaction, students are expected to build healthy relationships with peers, and schools need to create an environment conducive to students' social and personal development.